Load Chemical From Truck To Storage Tank Simulation Training Using Virtual Reality - Muhammad ‘Ammar Hafiz, Rozali (2023)
In environments with hazardous chemicals, where human error has been implicated in the majority of incidents, human performance is essential to ensuring safety and health. The effectiveness of knowledge and skill transfer has been a problem for both industry and academics. Technology for virtual reality (VR) is gaining popularity as a means of enhancing human performance. This study looks into what the industry knows and does before performing a routine task like loading or unloading a tanker. The purpose of this training application is to train operators in chemical industry the process of unloading chemical from truck to storage tank, which provide virtual procedure approach other than conventional methods such as class-based and on-the-job-training (OJT). Next, written procedures are sometimes hard for the workers to process and encourages them to ignore the important steps. Another issue is that the existing training materials are unable to inspire many situations, particularly those that include risks and hazards in both ordinary and unusual tasks and modules that call for extra monitoring. Due to the high expense of materials and equipment, certain training modules are also difficult to execute often. As a result, a VR training application for chemical loading has been developed to give employees the information and abilities they need to load chemicals from trucks into storage tanks. The users of this training application will see the actions to do in order to finish the course. To finish the training, users must interact with some of the buttons and other items that are included in the scenarios. The hazards triggered will be comparable to those in the actual world, making it simpler for users to become accustomed with it and have a better understanding of the circumstance. This VR application is developed with Unity and using the methodology ADDIE. The application has been evaluated and tested for its functionalities and effectiveness in chemical industry. The workers will have a fresh experience participating in real-life training thanks to this VR application. By fusing virtual information with actual data, this technology will help workers better envision and comprehend the problem by providing them with rich and interesting multimedia contents.